2005
DOI: 10.1111/j.1365-294x.2005.02549.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite and mitochondrial DNA analyses of the genetic structure of blacktip shark (Carcharhinus limbatus) nurseries in the northwestern Atlantic, Gulf of Mexico, and Caribbean Sea

Abstract: We investigated the genetic structure of blacktip shark (Carcharhinus limbatus) continental nurseries in the northwestern Atlantic Ocean, Gulf of Mexico, and Caribbean Sea using mitochondrial DNA control region sequences and eight nuclear microsatellite loci scored in neonate and young-of-the-year sharks. Significant structure was detected with both markers among nine nurseries (mitochondrial PhiST = 0.350, P < 0.001; nuclear PhiST = 0.007, P < 0.001) and sharks from the northwestern Atlantic, eastern Gulf of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
182
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(209 citation statements)
references
References 59 publications
14
182
2
5
Order By: Relevance
“…Other evidence that the adult phase is likely to be marine is provided by historical fisheries data of larger (estimated from landed weight) and presum- ably much older animals caught by longliners using bottom-set gear farther offshore. This pattern of smaller, juvenile sharks inshore and larger individuals offshore is similar to the ontogenetic patterns observed in other coastal species (Stevens et al 2000) such as blacktip sharks Carcharhinus tilstoni and bull sharks C. leucas (Keeney et al 2005, Yeiser et al 2008. Previous studies have suggested that G. garricki generally select turbid, freshwater and brackish reaches of rivers (Larson 2000), but the higher abundance of G. garricki in the fisheries we examined supports growing evidence for a greater tolerance to salinity than originally suspected (IUCN 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Other evidence that the adult phase is likely to be marine is provided by historical fisheries data of larger (estimated from landed weight) and presum- ably much older animals caught by longliners using bottom-set gear farther offshore. This pattern of smaller, juvenile sharks inshore and larger individuals offshore is similar to the ontogenetic patterns observed in other coastal species (Stevens et al 2000) such as blacktip sharks Carcharhinus tilstoni and bull sharks C. leucas (Keeney et al 2005, Yeiser et al 2008. Previous studies have suggested that G. garricki generally select turbid, freshwater and brackish reaches of rivers (Larson 2000), but the higher abundance of G. garricki in the fisheries we examined supports growing evidence for a greater tolerance to salinity than originally suspected (IUCN 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Tagging evidence and genetic information indicate that the western North Atlantic and Gulf of Mexico populations of Blacktip Sharks are separate (Keeney et al 2003(Keeney et al , 2005Bethea et al 2012), with little mixing occurring between the two basins. For this reason, the Blacktip Shark is managed as two stocks: the Gulf of Mexico and Atlantic Ocean stocks.…”
mentioning
confidence: 99%
“…Based on tagging and genetic studies, two stocks are defined in the stock assessment: the Atlantic stock distributed from Delaware to the Straits of Florida and the Gulf of Mexico stock. Although adult blacktip sharks are highly mobile and often disperse over long distances, tagging studies provide little evidence to support mixing between the two stocks (Keeney et al 2005;SEDAR 11 2006). They are philopatric (behavior of remaining in, or returning to, their birthplace) and return to their original nursery areas to give birth, which can result in subgroups of genetically distinct breeding stocks that overlap in geographic distributional ranges (Keeney et al 2003(Keeney et al , 2005.…”
Section: Blacktip Sharkmentioning
confidence: 99%